Lu et écrit chez Henri Michaux - Durnová, Anna (Verbum – Analecta Neolatina, 2005)
The work of Henri Michaux still represents a rich source of inspiration for both critics and readers. The paper focuses on the hermeneutic aspect of the double dimension of the voice; the transcribed one that emerges as the lyric subject in the text and the physical one that occurs during the act of reading. On example of use of the female lyric subject in the poem La Ralentie, the author tries to present the act of reading as an important dimension of interpretation, caused by what Ricoeur calls "distanciation". Two versions of the poem are compared: the text of Michaux and its recorded recitation by the actress Germaine Montero. The aim of the paper is to show, how the act of reading can modify the interpretation of the original version, whereas this possibility of more dimensional conceiving is to be understood as one of the main purposes of the Michaux's literary creation in general.